THE EFFECT OF BIOFERTILIZATION, ORGANIC NUTRIENT SPRAYING AND GLUTAMIC ACID ON SOME LETTUCE TRAITS - Al-Samah , Ayad; Al-Ubaidy, Ridha (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
A field experiment was conducted over two agricultural seasons, in a field of the Organic Fertilizers Project located in the Bani Zaid district of Shatra, under the Directorate of Agriculture of Dhi Qar. The factorial experiment included three factors conducted within a Randomized Complete Block Design (R.C.B.D) with three replications, 36 treatments per replicate. The study aimed to evaluate the effects of reducing mineral fertilizer application by 50% on lettuce (Lactuca sativa L.) growth, focusing on the combined impact of biofertilization with mycorrhiza and Azospirillum, along with foliar applications of an organic nutrient solution (Forteorgan) and glutamic acid. Conducted over two agricultural seasons (2022-2023 and 2023-2024). The results indicated that the combined treatment of mycorrhiza and Azospirillum inoculation, coupled with foliar applications of 4 ml L-1 Forteorgan and 500 mg L-1 glutamic acid, significantly enhanced leaf nitrogen percent in both seasons. Additionally, this combination improved leaf phosphorus and potassium percent, as well as total chlorophyll concentration, suggesting that integrating biofertilizers with reduced mineral fertilizer application can effectively promote nutrient uptake and photosynthesis in lettuce plants.